(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Background: Fibroid is the most common of all pelvic tumours, being present in 20 percent of women in the reproductive age group and increases with age.Obstetric cesarean hysterectomy is mostly done for indications deemed to be serious and life threatening to the patient and not amenable to conservative management. Case: A 27 years old lady was admitted in BSMMU with 3rd gravida 35 wks pregnancy with less fetal movement with fibroid uterus. Fibroid was diagnosed at her 21 weeks pregnancy by ultrasonogram. Caesarean section was done at 35+ weeks of pregnancy because of nonreactive CTG. After delivery of the baby and placenta, severe bleeding started. Caesarean hysterectomy was done. The mother and baby were healthy at the time of discharge. Conclusion: Very few patients needed cesarean hysterectomy in case of fibroids in pregnancy. However there is no question that cesarean hysterectomy save lives especially in case of bleeding that cannot be controlled by simpler measures. DOI: http://dx.doi.org/10.3329/bjog.v25i2.13746 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(2) : 87-89